Region Tourist and Recreation Complex Development - Tappaskhanova, Elizaveta Oyusovna; Mustafayeva, Zemfira Ammayevna; Tokmakova, Ruzana Azikovna; Kudasheva, Marzhan Zaurbekovna (Economy of Regions, 2015)
The subject matter of the research is the tourist and recreation complex of Kabardino-Balkar Republic. The purpose of the work is to provide solutions to problems of the republic tourist and recreation complex development. The results obtained from the study showed that in spite of the fact that in the region’s development certain positive steps are taken, according to the indicators of the tourism and recreation development, the region has not reach the level of the 1990th yet, the possibilities of this major sector of the republic economy remain not demanded. It is highlighted, that the most important factor in the tourist and recreation complex development is its infrastructure condition. It is recommended to use the model of the infrastructure management aimed at providing its effective functioning and development due to formation of interaction system at every power level through a network of the centers of the tourist and recreation complex development. In the article, the need for the use of the innovative approaches for the republic tourist and recreation complex development in the particular development of the new tourist directions are also found. For the purpose to improve the professional training of personnel for the tourism and recreation sphere, the need for a transition to multilevel training of personnel is proved. The main directions of the republic image development on the basis of designing and implementing of the regional program of its image development as the tourist territory and creation of the tourist information center are defined. Realization of all these problems allows to develop a highly effective and competitive tourist and recreation complex in Kabardino-Balkaria.